2021
DOI: 10.1016/j.msea.2020.140600
|View full text |Cite
|
Sign up to set email alerts
|

The high temperature mechanical properties and the correlated microstructure/ texture evolutions of a TWIP high entropy alloy

Abstract: Chemical composition of the as-homogenized material measured by XRF analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Consequently, stage B of the work hardening rate of the hetero-structured RA-500 sample maintains a near-constant value due to the severe deformation of coarsening grains, and subsequently the deformation of fine grains causes a gradual decrease in the work-hardening rate. Essentially, the enhanced strain hardening rate and work-hardening rate induced by heterogeneous matrix grains (i.e., soft coarse grains and fine hard grains) are similar to the TRIP effect (the occurrence of stress and strain hardening induced by hard fresh martensite and soft austenite [51][52][53][54]) and TWIP effect (changing the dislocation accumulation rate and hardening the slip system directly through the Hall-Petch effect [55,56]). For instance, the dislocation hardening of the stable fcc phase and increased ductility induced by transformation-induced hardening of the metastable hexagonal closed-packed (hcp) phase are widely researched in the FeMnCrCo-systems MEAs [53,54].…”
Section: Resultsmentioning
confidence: 86%
“…Consequently, stage B of the work hardening rate of the hetero-structured RA-500 sample maintains a near-constant value due to the severe deformation of coarsening grains, and subsequently the deformation of fine grains causes a gradual decrease in the work-hardening rate. Essentially, the enhanced strain hardening rate and work-hardening rate induced by heterogeneous matrix grains (i.e., soft coarse grains and fine hard grains) are similar to the TRIP effect (the occurrence of stress and strain hardening induced by hard fresh martensite and soft austenite [51][52][53][54]) and TWIP effect (changing the dislocation accumulation rate and hardening the slip system directly through the Hall-Petch effect [55,56]). For instance, the dislocation hardening of the stable fcc phase and increased ductility induced by transformation-induced hardening of the metastable hexagonal closed-packed (hcp) phase are widely researched in the FeMnCrCo-systems MEAs [53,54].…”
Section: Resultsmentioning
confidence: 86%
“…[ 9 ] Among the most promising groups are single‐phase FCC HEAs, which generally exhibit acceptable ductility yet mediocre yield strength due to their composition of a single austenite phase. [ 10–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9] Among the most promising groups are singlephase FCC HEAs, which generally exhibit acceptable ductility yet mediocre yield strength due to their composition of a single austenite phase. [10][11][12] The further development of HEAs has led to a noticeable surge in strengthening mechanisms by incorporating a second phase, thereby achieving both strength and ductility values at adequate levels. Strengthening mechanisms such…”
mentioning
confidence: 99%
“…[12,30,[36][37][38][39][40][41][42][43] HEAs are expected to exhibit outstanding high-temperature performance and could be ascribed to the "core effect" that is popular as sluggish diffusion. [6,[44][45][46] It has been reported that applying the AlCoCrFeNiTi 0.5 HEA as a coating on the substrate of Ti-6Al-4V led to an increase in the average hardness value from 304.3 HV (for substrate) to 706.3 HV (for coating). [47] That leads to an appreciable improvement in high-temperature wear resistance of the material.…”
Section: Introductionmentioning
confidence: 99%